Document delivery and resource sharing: A collaborative consortium approach by Indian agricultural libraries. Issue 1 (27th May 2017) - Singh, Neena
Abstract: Indian Agricultural Libraries are exploring new ways and collaborations to fullfil the information need of their patrons through resource sharing and delivering documents using online platform accessible 24X7. The article discusses Inter Lendig and Document Delivery Services (DDR) facilitated through a collaborative consortium Journal Gateway called CeRA under Indian National Agricultural Research System. CeRA the (Consortium for e-Resources in Agriculture) provides a platform for online acess to e-journals and inter lending. DDR Services has been established to share resources subscribed by individual libraries as well as consortium journals using the web portal. The article also discusses of the use of DDR services by patrons of the first Indian Agricultural University in the country. Reports that the student community were most active in using the platform for inter library loan and document request in comparison to the faculty researchers who were less dependent on document from other libraries.